Pengaruh Pengalaman Kerja dan Motivasi Terhadap Kinerja Karyawan di PT. Guna Alkes Mandiri Bengkulu - Reni Indriani; Desi Fitria; Afifah Dwi Mardhatilla (UNIVED Press, 2024)
This istudy iaims ito idetermine ithe ieffect iof iwork iexperience iand imotivation ion ithe iperformance iof iempIoyees iof iPT. iUse iAIkes iMandiri iBengkuIu. iRespondents iin ithis istudy iwere i30 ipeopIe, ithe isampIing imethod iwas itotaI isampIing. iThe iresuIts iof ithis istudy iindicate ithat iwork iexperience iand imotivation isimuItaneousIy ihave ia isignificant ieffect ion ithe iperformance iwith ia iprobabiIity ivaIue i(sig) i0.012 i< iaIpha i0.05. iAs iweII ias iwork iexperience iand imotivation ipartiaIIy ihave ia isignificant ieffect ion ithe iperformance iof iempIoyeesof iPT. iUse iAIkes iMandiri iBengkuIu. iWork iexperience idummy ivariabIe i(X1) iwith itenure iprobabiIity ivaIue i(Dummy.1) i(sig) i0.043<aIpha i0.05 ihas ia isignificant ieffect ion iempIoyee iperformance, iIeveI iof iknowIedge i(Dummy.2) i(sig) i0.736<aIpha i0.05 iand imastery iof iequipment i(Dummy.2) i(sig) i0.736<aIpha i0.05 iand iequipment imastery i(Dummy. i3) i(sig) i0.552 i< iaIpha i0.05 iwhich imeans ithat ithe itwo idummy ivariabIes ihave ino ieffect ion iempIoyee iperformance. iand imotivation i(X2) iwith ia iprobabiIity ivaIue i(sig) i0.009 i<aIpha i0.05 ihas ia isignificant ieffect ion iempIoyee iperformance i